Global Economic Prospects and the Developing Countries 1995 - World Bank (Washington, DC: World Bank, 2019)
This year’s report derives its main theme from a fundamental change that is taking place in the world economy today – globalization. This change is being driven both by widespread adoption of market liberalization policies and by technological change that is fast eroding physical barriers to international transactions. The report also reviews the prospects for developing countries in the context of their increasing integration into world markets for goods, services, and capital, highlighting the new opportunities and challenges that arise from closer international economic integration. The process of integration also brings frictions, the report notes, which requires closer monitoring and quicker policy responses at the country, regional, and global levels.